Targeted PET imaging of chemokine receptor 2-positive monocytes and macrophages in the injured heart - Heo, Gyu Seong; Bajpai, Geetika; Li, Wenjun; Luehmann, Hannah P.; Sultan, Deborah H.; Dun, Hao; Leuschner, Florian; Brody, Steven L.; Gropler, Robert J.; Kreisel, Daniel; Lavine, Kory J.; Liu, Yongjian (Journal of nuclear medicine, 2020)
Proinflammatory macrophages are important mediators of inflammation after myocardial infarction and of allograft injury after heart transplantation. The aim of this study was to image the recruitment of proinflammatory chemokine receptor 2-positive (CCR2+) cells in multiple heart injury models. Methods: 64 Cu-DOTA-extracellular loop 1 inverso (ECL1i) PET was used to image CCR2+ monocytes and macrophages in a heart transplantation mouse model. Flow cytometry was performed to characterize CCR2+ cells. Autoradiography on a human heart specimen was conducted to confirm binding specificity. 64 Cu- and 68 Ga-DOTA-ECL1i were compared in an ischemia-reperfusion injury mouse model. Results: 64 Cu-DOTA-ECL1i showed sensitive and specific detection of CCR2+ cells in all tested mouse models, with efficacy comparable to that of 68 Ga-DOTA-ECL1i. Flow cytometry demonstrated specific expression of CCR2 on monocytes and macrophages. The tracer binds to human CCR2. Conclusion: This work establishes the utility of 64 Cu-DOTA-ECL1i to image CCR2+ monocytes and macrophages in mouse models and provides the requisite preclinical information to translate the targeted clinical-grade CCR2 imaging probe for clinical investigation of heart diseases.